Implementasi Kegiatan Intrakurikuler Di PAUD Al-Islam Riyadhul Irfan Kecamatan Kadungora Kabupaten Garut - Aliyah, Siti; Marselin, wini; Ramdiani, Siti (LP2M STAI Al-Musaddadiyah Garut, 2025)
This research is motivated by preliminary observations conducted on October 11, 2024, at PAUD Al-Islam Riyadhul Irfan, Rancasalak Village, Kadungora District, Garut Regency. The Intracurricular Program includes learning activities related to subjects. Every implementation of this activity is mandatory for students with different abilities according to existing provisions to enhance basic competencies that students must possess, carried out continuously every day according to a scheduled activity plan. The purpose of this research is to determine the implementation of Intracurricular Activities at PAUD Al-Islam Riyadhul Irfan and the obstacles in implementing them. This research uses a qualitative and descriptive approach that describes events faced and currently occurring. The subjects of this research are all students at PAUD Al-Islam Riyadhul Irfan. Data collection techniques consist of observation, interviews, and documentation. Data analysis techniques involve data reduction, data presentation, and conclusion drawing. ntracurricular activities are implemented through several steps, starting with developing Learning Outcomes (CP) into Learning Objectives (TP), resulting in a series of systematically and logically arranged Learning Objectives. To compile ATP, educators can design their own based on Learning Outcomes or develop examples provided by the government Keywords: Intracurricular Activities; Implementation; Early childhood